2008
DOI: 10.1159/000126066
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis: Risk Factors for the Recurrence of Chronic Rhinosinusitis Based on 5-Year Follow-Up after Endoscopic Sinus Surgery

Abstract: Background: Chronic rhinosinusitis (CRS) is one of the most frequent chronic diseases in the US, and little is understood about its pathogenesis. This study was conducted to characterize, retrospectively, the clinical, objective and immunological parameters that accompany recurrence of CRS during long-term follow-up after surgery. Methods: Fifty-six patients with CRS who had undergone endoscopic sinus surgery were followed up for 5 years after the surgery. The CRS parameters chosen were as follows: history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
164
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(187 citation statements)
references
References 38 publications
10
164
3
4
Order By: Relevance
“…1 Mucosal eosinophilia (defined as more than 120 cells per high-power magnification field) is reported to most strongly correlate with chronic rhinosinusitis recurrence. 8 The association of eosinophilic chronic rhinosinusitis with asthma is widely accepted. 10 The present study also found a higher prevalence of asthma in eosinophilic chronic rhinosinusitis patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Mucosal eosinophilia (defined as more than 120 cells per high-power magnification field) is reported to most strongly correlate with chronic rhinosinusitis recurrence. 8 The association of eosinophilic chronic rhinosinusitis with asthma is widely accepted. 10 The present study also found a higher prevalence of asthma in eosinophilic chronic rhinosinusitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chronic rhinosinusitis with nasal polyps was subdivided into eosinophilic and non-eosinophilic chronic rhinosinusitis according to the degree of eosinophilic infiltration into sinus mucosal tissue ( Figure 1). 8 Before surgery, all patients underwent CT imaging and the peripheral eosinophil count, total serum immunoglobulin E (IgE) and respiratory function were measured. Computed tomography scans were evaluated by an otolaryngologist and a radiologist who were blinded to the disease subtype and staged according to the Lund-MacKay scoring system.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils are multifunctional leukocytes implicated in the pathogenesis of various inflammatory processes, including allergic diseases, bronchial asthma, chronic rhinosinusitis (CRS), helminth and viral infections, tumor immunity, and tissue injury [1,2,3]. The mere presence of eosinophils, as in the normal intestinal mucosa [4], does not lead to pathology.…”
Section: How Are Eosinophils Activated To Release Proinflammatory Andmentioning
confidence: 99%
“…The analysis of the available reports indicates that mostly disease severity, comorbidities, medications used prior to surgery and a history of previous surgical treatment due to rhinosinusitis are the preoperative factors that influence surgery [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%